The degree to which female teachers of the first three grades in Zarqa first employ alternative assessment tools from their own point of view - Alasad, Munera Ahmad Abed (Journal of Educational and Psychological Sciences, 2023)
This study aimed to find out the degree to which teachers of the first three grades in the first Zarqa Education Directorate employ alternative assessment tools from their own point of view, and to identify the differences in the degree to which they practice them according to the variable years of experience. The descriptive survey method was used, and a questionnaire was designed that included (45) paragraphs and was divided into five areas (paper-and-pencil evaluation, performance-based evaluation, observational evaluation, self-review evaluation, and communication evaluation). 137) Parameter they were selected by simple random method and the results indicated that the total degree of the use of the parameters of the alternative assessment tools for the domains was high. With an average of (3.93), the results also showed that there were no statistically significant differences in the degree of female teachers’ use of the first three grades of alternative assessment tools due to the variable years of experience. In light of the results, the study recommended the necessity of adopting alternative assessment tools in the process of evaluating students in the school.